(untitled) - Council of Fashion Designers of America (New York, 2007)
This creative crescendo continues with the evolution of the major names in American fashion during 1960s and 1970s and goes on to explore the achievements of our country’s marquee stars of the 1980s and 1990s. American Fashion culminates with a look at contemporary talents who export their individual visions internationally. Chronicling the designers, icons, publications, and events that shaped fashion for more than 70 years, this is the essential compendium of the rich and vivid story that is American fashion.
Keywords: Fashion designers,Nhà thiết kế thời trang; United States,Mỹ